Socio-Economic, Political and Cultural Life in the Period of Amir Temur and Temuries (Zien Journal of Social Sciences and Humanities, 2023)
The main purpose of this article is to represent a special period in the culture of Central Asia, the era of Timur and the Timurids, to provide information about the socio-economic development of the culture of this period formed on the basis of the principles of strong statehood founded by Timur.